2022
DOI: 10.1111/1759-7714.14411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analytical performance of the Oncomine dx target test focusing on bronchoscopic biopsy forceps size in non‐small cell lung cancer

Abstract: Background Next‐generation sequencing (NGS) has been implemented in clinical oncology to analyze multiple genes and to guide targeted therapy. Although the pathological diagnosis and biomarker tests for patients with advanced lung cancer have mostly been obtained with small biopsy samples, especially with bronchoscopic approaches, the performance for NGS with respect to the different sizes of biopsy forceps remains little known. Methods We retrospectively reviewed consecutive patients with non‐small cell lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A recent report suggests that a multi-gene panel test performed prior to the initiation of systemic treatment can potentially enhance prognosis by detecting a wider range of driver oncogene alterations than multiple single-gene tests [5], and therefore the improvement in the submission rate and success rate of multi-gene panel tests is expected to contribute to a good prognosis for patients with NSCLC in clinical practice. This improvement has come from various efforts to submit samples of appropriate quantity and quality [13,16], learning from other reports [12,17], the availability of AmoyDx-multi testing, and improved handling proficiency in laboratory inspections. A previous report showed that tissue size and tumor cell content were significantly associated with a good ODxTT success rate in small biopsy samples, especially when specimens with a tissue size of 4 mm 2 or larger and a tumor cell content of 20% or more are available [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that a multi-gene panel test performed prior to the initiation of systemic treatment can potentially enhance prognosis by detecting a wider range of driver oncogene alterations than multiple single-gene tests [5], and therefore the improvement in the submission rate and success rate of multi-gene panel tests is expected to contribute to a good prognosis for patients with NSCLC in clinical practice. This improvement has come from various efforts to submit samples of appropriate quantity and quality [13,16], learning from other reports [12,17], the availability of AmoyDx-multi testing, and improved handling proficiency in laboratory inspections. A previous report showed that tissue size and tumor cell content were significantly associated with a good ODxTT success rate in small biopsy samples, especially when specimens with a tissue size of 4 mm 2 or larger and a tumor cell content of 20% or more are available [17].…”
Section: Discussionmentioning
confidence: 99%
“…These findings will guide pulmonologists in determining the appropriate sampling devices such as selecting the GS size, adding TBNA, or switching to other methods, including the non-GS method. This should consider not only diagnostic performance, but also the cost and amount of tissue samples required for molecular analysis in advanced lung cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably because the number of tumor cells was similar in both cases. In a previous report, the success rate of ODxTT in the group that performed TBB using only small forceps was 70% [ 17 ]. In the present study, the success rate of the ODxTT in the ultrathin bronchoscopy cases was not inferior, and it was possible to collect specimens suitable for ODxTT.…”
Section: Discussionmentioning
confidence: 99%